Secure Data Transfer: Based on Steganography and Visual Cryptography - D.Rajapriya, Rini K (International Journal of Engineering and Computer Science, 2017)
Secure data transfer is one of the most important concern with the internet users who are transmitting highly secures information through internet. We have various technologies available to overcome this issue and the main includes the steganographic and visual cryptographic techniques. Using steganography, messages senders can hide their secure data in image, audio or video files. Images are widely used because of its availability as well as there are millions of images are transmitted through internet in each fractions of second, which makes them an excellent cover for secure messages. Steganography got a challenger in the form of steganalysis who can recreate the secure data from the message using various steganalysis techniques. Visual cryptography is another important method which provides 2 way authentication, where the user the needs to get all the shares of the image to complete the required action. In this paper, we have presented a system which uses both the concepts of steganography and visual cryptography to securely transfer data. The secured message is hidden in the image using the steganographic LSB and then the images are partitioned into shares and send separately to the receiver. The receiver needs all the shares to recover the image with hidden message and then the message to be decoded from the image.